Early metastable assembly during the stress-induced formation of worm-like amyloid fibrils of nucleic acid binding domains of TDP-43 - Pillai, Meenakshi; Jha, Santosh Kumar (Biochemistry, 2020)
TDP-43 protein travels between the cytosol and the nucleus to perform its nucleic acid binding functions through its two tandem RNA recognition motif domains (TDP-43(tRRM)). When exposed to various environmental stresses, it forms abnormal aggregates in the cytosol of neurons, which are the hallmarks of amyotrophic lateral sclerosis and other TDP-43 proteinopathies. However, the nature of early structural changes upon stress sensing and the consequent steps during the course of aggregation are not well understood. In this study, we show that under low-pH conditions, mimicking starvation stress, TDP-43(tRRm) undergoes a conformational opening reaction linked to the protonation of buried ionizable residues and grows into a metastable oligomeric assembly (called the ``low-pH form'' or the ``L form''). In the L form, the protein molecules have disrupted tertiary structure, solvent-exposed hydrophobic patches, and mobile side chains but the native-like secondary structure remains intact. The L form structure is held by weak interactions and has a steep dependence on ionic strength. In the presence of as little as 15 mM KCl, it fully misfolds and further oligomerizes to form a beta-sheet rich ``beta form'' in at least two distinct steps. The beta form has an ordered, stable structure that resembles worm-like amyloid fibrils. The unstructured regions of the protein gain structure during L (sic) beta conversion. Our results suggest that TDP-43(tRRm) could function as a stress sensor and support a recent model in which stress sensing during neurodegeneration occurs by assembly of proteins into metastable assemblies that are precursors to the solid aggregates.